The 1st Euro-Mediterranean Workshop: Natural Products in Health and Diseases: Cairo, Egypt, March 2, 2015 - Kamal D. Moudgil; Ashraf A. Khalil (Elsevier, 2016)
Natural plant products have been used for centuries for health maintenance and treatment of a variety of diseases in various traditional systems of medicine in Egypt and other African countries, India, China, and other countries around the world. Over the past several decades, the popularity of herbal and other natural products has gradually increased in many western countries. Despite the increasing popularity of natural products, both the public and the professionals are skeptical about the use of these products. Reasons for this skepticism include, but are not limited to, the lack of proper documentation about the source and formulations used; standardization of the composition, batch-to-batch consistency, documented safety of herbal products; and information about the mechanisms of action of these products. The 1st Euro-Mediterranean Workshop: Natural Products in Health and Diseases was organized by the Euro-Mediterranean Association of Life Sciences (EMALS) and various other local organizations to review and discuss the above-mentioned strengths and limitations of the use of natural products. The aim of this workshop was to share best practices and expertise about natural products, and to identify opportunities for collaboration among researchers, health professionals, and business personnel in a productive atmosphere.